Method of Reading Spatial Indicators of Technological Disasters - Hurol Al, Yonca (UCEAT Chamber of Architects, 1998)
The aim of this article is to present the method, which was used to find the victims of compulsory migration in the city of Van, to be able to provide them better shelters.
It was necessary to develop a method to be able to find the victims of the compulsory migration before designing shelters for them and building those shelters as self-built housing.
Keywords: conflict, compulsory migration, spatial indicators, research method